Evaluation of Fetal Breathing-Related Nasal Fluid Flow Doppler in the Third Trimester in Pregnant Women with Fetal Growth Restriction: Preliminary Observations - Rzayeva, Gunay; Kale, İbrahim; Arısoy, Resul; Muhcu, Murat (Zeitschrift für Geburtshilfe und Neonatologie, 2024)
Objective To investigate the fetal breathing-related nasal fluid flow Doppler waveforms as an indicator of fetal respiratory function in fetuses diagnosed with fetal growth restriction (FGR) in the third trimester.Materials and Methods This prospective, non-interventional case-control study was conducted on 96 pregnant women, including 23 pregnant women diagnosed with FGR in the third trimester as the FGR group and 73 healthy pregnant women with fetuses appropriate for gestational age (AGA) as the control group. Fetal breathing-related nasal fluid flow Doppler was examined in the fetuses of the participants. Inspiration and expiration duration, inspiration and expiration peak velocity, total breathing duration, and number of fetal breaths per minute were calculated.ResultsBoth groups were similar in terms of the duration of inspiration, duration of expiration, and total breathing duration (p=0.463, p=0.711, p=0.520, respectively). Peak inspiratory velocity and peak expiratory velocity were significantly lower in the FGR group than in the control group, and the number of fetal breaths per minute was similar in both groups (p=0.027, p=0.012, p=0.768, respectively). When participants were regrouped into those whose newborn was admitted to the neonatal intensive care unit (NICU) after birth and those who were not, all fetal nasal fluid flow Doppler parameters were similar in both groups.Conclusions Although the number of participants was too small to draw a definitive conclusion, FGR appears to be associated with a decrease in peak inspiratory and expiratory velocity. The clinical significance of changes in fetal breathing-related nasal fluid flow Doppler parameters in FGR is as yet unclear, and their use in clinical follow-up and predicting unfavorable perinatal outcomes are the subjects of future research.
Keywords: fetal breath movement; fetal growth restriction; fetal nasal fluid flow Doppler